2019
DOI: 10.3390/toxins11010017
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus bulgaricus or Lactobacillus rhamnosus Suppresses NF-κB Signaling Pathway and Protects against AFB1-Induced Hepatitis: A Novel Potential Preventive Strategy for Aflatoxicosis?

Abstract: Aflatoxin B1 (AFB1), a mycotoxin found in food and feed, is immunotoxic to animals and poses significant threat to the food industry and animal production. The primary target of AFB1 is the liver. To overcome aflatoxin toxicity, probiotic-mediated detoxification has been proposed. In the present study, to investigate the protective effects and molecular mechanisms of Lactobacillus bulgaricus or Lactobacillus rhamnosus against liver inflammatory responses to AFB1, mice were administered with AFB1 (300 μg/kg) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Unsurprisingly, the upregulation of TLR-2/4 was verified at different doses of AFs ( Muhammad et al, 2018b ; Huang et al, 2019 ; Wang et al, 2019 ). Several papers found that the mRNA and protein expression of NF-κB was upregulated in hepatocytes after exposure to AFs ( Ma et al, 2015 ; Oskoueian et al, 2015 ; Muhammad et al, 2018b ; Chen et al, 2019a ; Huang et al, 2019 ; Zhang et al, 2019 ). NF-κB binds to an inhibitory protein called IκB in the resting state and remains sequestered in the cytoplasm.…”
Section: Afs Amplify Hepatotoxicity In the Shape Of A Vice Feedback Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, the upregulation of TLR-2/4 was verified at different doses of AFs ( Muhammad et al, 2018b ; Huang et al, 2019 ; Wang et al, 2019 ). Several papers found that the mRNA and protein expression of NF-κB was upregulated in hepatocytes after exposure to AFs ( Ma et al, 2015 ; Oskoueian et al, 2015 ; Muhammad et al, 2018b ; Chen et al, 2019a ; Huang et al, 2019 ; Zhang et al, 2019 ). NF-κB binds to an inhibitory protein called IκB in the resting state and remains sequestered in the cytoplasm.…”
Section: Afs Amplify Hepatotoxicity In the Shape Of A Vice Feedback Lmentioning
confidence: 99%
“…Although upstream signaling events differ between individual receptors, the IκB-kinase (IKK) complex is eventually activated, which subsequently inactivates the inhibitory chaperone IκBα of NF-κB ( Afonina et al, 2017 ). Several research papers demonstrated that the expression level of IκB was inhibited in AFs group ( Chen et al, 2019a ; Huang et al, 2019 ). The mRNA level of IKK increased, but it was not significant ( Mughal et al, 2017 ).…”
Section: Afs Amplify Hepatotoxicity In the Shape Of A Vice Feedback Lmentioning
confidence: 99%
“…The reason why high ADE concentrations could in uence cell viability may be due to the high levels of enzymes existing in ADE to damage cells, so low ADE concentration is selected in this study. It was reported that supplementation of L. bulgaricus or L. rhamnosus could produce signi cant protective effect against AFB 1 -induced liver damage and in ammatory response (Chen et al 2019). Moreover, the addition of compound probiotics and mycotoxin-degradation enzyme could prevent broilers from damages induced by AFB 1 (Zuo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al researched the ability of Bacillus subtilis ANSB060 to detoxify AFs. Their results showed that B. subtilis improved the growth performance and meat quality of broilers [ 138 ]. The levels of AF residues in the livers of broilers consuming naturally moldy peanut meal were also decreased [ 134 ].…”
Section: Application Of Microbial Detoxificationmentioning
confidence: 99%
“…The levels of AF residues in the livers of broilers consuming naturally moldy peanut meal were also decreased [ 134 ]. Chen et al found that oral Lactobacillus bulgaricus or Lactobacillus rhamnosus ingestion can significantly prevent liver injury induced by AFB1, and reduce histopathological changes and inflammation by elevating the expression of NF-κB p65 [ 138 ]. Feeding with Lactobacillus plantarum 299v can decrease the contents of serum lactate dehydrogenase and alanine aminotransferase in the liver and increase the body weight of broilers by about 20%-55%, bringing economic benefits [ 139 ].…”
Section: Application Of Microbial Detoxificationmentioning
confidence: 99%